Estudo das propriedades mecânicas de interface aplicadas em revestimentos espessos obtidos por aspersão térmica - Alves, Yuri de Melo (2011)
This work appears as an experimental attempt to verify the validity of the theoretical model used to interface ratio proposed by Chicot and Lesage. For this, we present a study on the mechanical properties of interface from the instrumented penetration tests. One of the important points of the study is related to the characteristics of materials with micro deformations and influence of defects on the mechanical properties. Discussions are developed concerning the intrinsic properties, especially the behavior of elastic modulus for different situations in which the materials are. Were used for development work, specimens taken from oil pump stem, which are used in oil production equipment. These stems were coated with two types of materials, the basis of a NiCr alloy and another with Al, both obtained by thermal spray process (arc spray). Using instrumented penetration test was carried out indentations in the coatings, substrate and interface of each sample. With these results, we applied the theoretical model interfacial and later tried to verify itsvalidity.